Is the use of letrozole to induce ovulation teratogenic? - Gill, Simerpal Kaur (College of Family Physicians of Canada, 2008)
QUESTION A patient of mine has been prescribed letrozole to induce ovulation; however, a recent release from the Food and Drug Administration contraindicates the use of letrozole in premenopausal women owing to teratogenicity. Does the use of letrozole increase the risk of a child being born with a birth defect? ANSWER The use of letrozole to induce ovulation has not been associated with an increased risk of a child being born with a birth defect; in contrast, the use of clomiphene citrate in pregnancy is associated with intrauterine growth restriction.